Biodiversity of fish species composition in coastal waters of Ha Tinh province - Trung, Hoàng Đình; Ngô, Thị Bảo Châu (Hue University Journal of Science: Natural Science, 2025)
The study was conducted through four surveys from May 2023 to February 2025 at eight sampling sites. A total of 206 fish species were recorded, belonging to 129 genera, 64 families, and 20 orders across two subclasses (Chondrichthyes and Actinopterygii). Among them, the order Acanthuriformes was dominant, comprising 45 species (21.84% of the total species) and 14 families (21.88% of the total families). Besides, 171 species listed in the IUCN Red List (2024) under various threat categories were identified: one species as Endangered (EN), six as Vulnerable (VU), 150 as Least Concern (LC), four as Near Threatened (NT), and ten as Data Deficient (DD). According to the Vietnam Red Data Book (2007), one species (0.49%) was classified as Critically Endangered (CR). Three species (accounting for 1.46%) are listed in the Vietnam Red Data Book (2024) under the Vulnerable (VU) category. Additionally, 24 species (11.65%) were identified as having economic value, and 25 species (12.14%) are commonly cultured for commercial purposes. These findings provide important baseline data for the sustainable management and conservation of fish resources in the region.